Efficacy of granular applications of clothianidin and nitenpyram against Aphis gossypii (Glover) and Apolygus lucorum (Meyer-Dür) in cotton fields in China. (December 2015) - Zhang, Peng; Zhang, Xuefeng; Zhao, Yunhe; Ren, Yupeng; Mu, Wei; Liu, Feng
Abstract: With the widespread use of transgenic Bt-cotton in China and the reduction in the amount of broad-spectrum insecticides used in cotton production, piercing-sucking insects, including mirids, aphids, thrips and whiteflies, have become major pests and have led to significant yield losses. Although neonicotinoid insecticidal seed or granular treatments at sowing have been suggested as a control method, the season-long efficacy of these treatments against pests and their natural enemies remains unknown. This study, conducted during 2013–2014 in Shandong, demonstrates that granular treatments of both clothianidin and nitenpyram at sowing can prevent yield losses and Aphis gossypii (Glover) and Apolygus lucorum (Meyer-Dür) infestations during the seedling to blooming stages of Bt-cotton. Clothianidin and nitenpyram granular treatments maintained A. lucorum at densities that were below the average threshold for economic relevance. Clothianidin (applied at a rate of 3.6 kg a.i./ha) provided the longest and best control within 115 days after planting and improved the yield. These granular treatments also reduced the population densities of Frankliniella intonsa (Trybom) and Bemisia tabaci (Gennadius) but decreased the population densities of Harmonia axyridis (Pallas) and Propylea japonica (Thunberg), an effect that may be due more to a lack of prey than to insecticide toxicity. Granular treatments with clothianidin and nitenpyram produced systemic insecticidal effects on A. gossypii and A. lucorum, with the former being slightly more effective than the latter. The use of granular treatments of these insecticides at sowing may represent an important component of integrated management practices against piercing-sucking insects in Bt-cotton. Highlights: Efficacy of granular clothianidin and nitenpyram on pests was tested in 2013–2014. Clothianidin and nitenpyram prevented Aphis gossypii and Apolygus lucorum infestations. Clothianidin and nitenpyram prevented cotton yield losses. The pest control effects lasted until the Bt-cotton blooming season. Clothianidin and nitenpyram caused reductions in lady beetle population densities.